1972
DOI: 10.1159/000178257
|View full text |Cite
|
Sign up to set email alerts
|

Hormones and Water Movement Through the Vertebrate Intestine

Abstract: A review of the current state of knowledge and speculation on fluid absorption by the gastro-intestinal tract of vertebrates and more specifically the role of hormones in fluid movement has been made. The effect of hormones on water transport, active sodium transport and the electrical characteristics of poikilotherm vertebrate, bird and mammal intestine, both in vivo and in vitro are considered. Special reference is made to the effect of aldosterone on the absorption of fluid. Data indicate that while aldoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1973
1973
1982
1982

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…This suggests that these hormones have no synergistic effects on intestinal absorption. This is not surprising as stimulation of fluid and ion trans¬ port in the small intestine by adrenal steroids has only sometimes been observed (Matty & Noble, 1972).…”
Section: Resultsmentioning
confidence: 98%
“…This suggests that these hormones have no synergistic effects on intestinal absorption. This is not surprising as stimulation of fluid and ion trans¬ port in the small intestine by adrenal steroids has only sometimes been observed (Matty & Noble, 1972).…”
Section: Resultsmentioning
confidence: 98%
“…Aldosterone stimulates mucosal transfer of water and sodium in the rat small intestine (Crocker & Munday, 1969) and absorption of sodium by the rat colon (Edmonds, 1972). The effects of aldosterone on the proximal small intestine are not always easy to demonstrate without prior suppression of endogenous aldo¬ sterone levels (Matty & Noble, 1972). Angiotensin also stimulates fluid and sodium transport by the jejunum of rats sensitized by previous adrenalectomy and nephrectomy (Crocker & Munday, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…Although recent reviews of hormonal influences on intestinal absorption and metabolic functions emphasize the importance of effects on water and electrolyte absorption by the mammalian gut (Gelb & Gerson, 1969;Levin, 1969;Matty & Noble, 1972), the adenohypophysial hormones have not received much attention in this context. Prolactin (PRL) is known to decrease intestinal ion and water permeability in seawater eels (Utida, Hirano, Oide, Ando, Johnson & Bern, 1972;Utida & Hirano, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence implicating the action of several hormones on intestinal absorption of water and electrolytes (Gelb & Gerson, 1969;Levin, 1969;Matty & Noble, 1972). Recently, we have demonstrated that pituitary and placental lactogenic hormones caused dramatic increases in mucosal fluid and ion transport by the rat intestine (Ramsey & Bern, 1972;Mainoya, Bern & Regan, 1974;Mainoya, 1975e).…”
Section: Introductionmentioning
confidence: 98%
“…Matty & Noble, 1972), but there appears to have been no investigation of the effects of pregnancy and lactation on intestinal fluid and NaCl transport. In view of the important increases in serum levels of prolactin during oestrus, pregnancy and lactation (Amenomori, Chen & Meites, 1970), the present investigation of the ability of the rat jejunum to transport fluid and electrolytes during these various physiological states was undertaken.…”
Section: Introductionmentioning
confidence: 99%